Strategies for Addressing the Growing Integration of Artificial Intelligence (AI) in The Learning Process - Muhammad Zuljalal Al Hamdany; Bustanul Iman RN (CV. Creative Tugu Pena, 2025)
This descriptive qualitative study examines the use of artificial intelligence (AI), particularly ChatGPT, in the learning process at Universitas Islam Negeri (UIN) Palopo, Indonesia, and identifies strategies for integrating AI into higher education responsibly. Data were collected through observation, semi structured interviews, and an open-ended questionnaire involving 16 lecturers and students with experience using AI in teaching and learning, selected through purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldana. The findings show that AI has considerable potential to enhance the quality of learning by supporting independent study, improving digital literacy, and enabling more adaptive and personalized instruction, while also strengthening lecturer and students’ interaction by freeing class time for deeper discussion. At the same time, participants raised concerns about limited technological literacy, the risk of overreliance on AI, and the absence of clear institutional policy on AI use. The study recommends that UIN Palopo and similar institutions develop structured digital literacy training and formal policies on the ethical use of AI, so that AI functions as a supportive partner rather than a substitute for the human and critical dimensions of higher education.